An Update on Anti-COVID-19 Vaccines and the Challenges to Protect Against New SARS-CoV-2 Variants - Fábio Mambelli; Ana Carolina V. S. C. de Araujo; Jéssica P. Farias; Kivia Q. de Andrade; Luis C. S. Ferreira; Paola Minoprio; Luciana C. C. Leite; Sergio C. Oliveira (Pathogens)
The COVID-19 pandemic has posed a significant threat to global health systems, with extensive impacts across many sectors of society. The pandemic has been responsible for millions of deaths worldwide since its first identification in late 2019. Several actions have been taken to prevent the disease, including the unprecedented fast development and global vaccination campaigns, which were pivotal in reducing symptoms and deaths. Given the impact of the pandemic, the continuous changes of the virus, and present vaccine technologies, this review analyzes how, so far, we have met the challenge posed by the emergence of new variants and discusses how next-generation pan-coronavirus vaccines, with enhanced longevity and breadth of immune responses, may be tackled with alternative administration routes and antigen delivery platforms. By addressing these critical aspects, this review aims to contribute to the ongoing efforts to achieve long-term control of COVID-19, stimulating the discussion and work on next-generation vaccines capable of facing future waves of infection.